Kemampuan Technopreneur Melalui Project Based Learning dengan E-Modul Kewirausahaan berbasis Book Creator - Sari, Wardani Purnama; Rahmania, Meri; Wati, Wati (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to test the effect of project based learning with the help of e-module entrepreneurship based on book creator on Technopreneur ability of Economic Education Students UIN Suska Riau. This study is a Quasi experiment using a pretest-posttest control group design (Creswell, 2014). This study uses the Project Based Learning model for Technopreneur ability assisted by E-Module Entrepreneurship Based on Book Creator. This research was conducted in the Economic Education Study Program UIN Sultan Syarif Kasim Riau. In this study there are two classes, namely the experimental class and the control class. The results of the study showed that the hypothesis testing obtained t count greater than t table, which is 2.49 greater than 1.66, so the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The N-Gain value in the Experiment class is 0.41 in the medium category, namely 41% of the effect of using the Project Based Learning learning model with E- Module Entrepreneurship Based on Book Creator on Technopreneur ability. With the acceptance of H1 in the hypothesis testing, the conclusion in this study is that there is a significant influence.